PENGARUH PEMBERIAN EKSTRAK BUAH JAMBU BIJI (Psidium guajava L.) TERHADAP JUMLAH SEL LEYDIG TIKUS PUTIH (Rattus norvegicus) YANG DIPAPAR ASAP ROKOK - LAILY ‘ULYA NURUL ‘ILMI, 061511133081 (2019)
The purpose of this research is to prove the effect of guava fruit extract to the to the amount of Leydig cellstestes in rats exposed to cigarette smoke. This experimental research using 25 rats which criteria 2-3 month old, male and average weight of 150-200 gram. Group of negative control (K-) was given CMC Na 0.5% 2 ml without exposed by cigarettes smoke, group of P0 was exposed with cigarette smoke and given CMC Na 0.5% 2 ml, treatment groups P1, P2 and P3 treated with guava fruit extract at dose of 3.78 mg/200gBB, 7.56 mg/200gBB, 11.34 mg/200gBB and exposed to cigarette smoke. Exposure cigarette smoke had been given three pieces cigarettes per group each day. All Treatment and exposure cigarette smoke was given about 45 days. The result showed that guava fruit extract has potential improved the amount of Leydig cells exposed to cigarette smoke in the highest dose 11.34 mg/200gBB. Based on statistical data analysis using Analysis of Variance (ANOVA) it showed significant different (p=0.000) with mean ± SD as follows: K(-)6.20d ± 0.32; K(+) 2.00a ± 0.14; P1 3.88b ± 0.70; P2 4.32b ± 0.42; P3 5.32c ± 0.39, further analysis using Duncan Multiple Range Test (DMRT). The conclusion of this research showed that guava fruit extract could improve Leydig cells count on testes in rats exposed to cigarettes smoke.